The Odeon: essays on poetry - Tobin, Daniel (Louisiana State University Press, 2025)
"The Odeon, a new volume of essays by the celebrated poet and critic Daniel Tobin, takes its title from the classical Greek and Roman buildings designed for the presentation of musical and poetic compositions. Organized around the question of "sensibility"--with its various social, philosophical, and aesthetic connotations--the collection presents a sequence of related essays exploring both resonances and dissonances in the traditions of modern and contemporary poetry. Although Tobin surveys a broad spectrum of works--ranging from John Donne and Emily Dickinson to writers from the twenty-first century such as Mark Doty, Louise Glück, and Carl Phillips--his emphasis remains on details of poetic practice, technique, metaphysical outlook, and artistic aspiration. What most informs these essays is Tobin's own practice as a poet, his own sensibility, which is at once eclectic and yet very much calibrated to matters of what one theologian termed "ultimate concern." The Odeon offers an incisive foray into the state of the art of poetry in our time"-- Provided by publisher